Parameters for Inherently Homogeneous Sintering Processes. Issue 9 (17th March 2015) - Raether, Friedrich
<x xml:space="preserve">Abstract</x> Thermodynamic criteria are introduced to calculate the driving force for the formation of heterogeneous metastable states during sintering. As already shown for one special case of liquid phase sintering, these metastable states significantly affect the reliability of sintered ceramics. Inherently safe sintering processes are proposed, providing a homogeneous evolution of microstructure. A desintering parameter is defined which can be used for a quantitative evaluation of different sintering processes in terms of their tendency for formation of heterogeneity. The desintering parameter has been calculated using sintering simulations in 3D representative volume elements. For that, a deterministic model has been developed. It considers interface energy minimization and grain growth for random arrangements of particles. Computational effort could be significantly reduced by periodic continuation of the microstructure at the sides of the RVE. Basic parameters controlling inherently homogeneous sintering are presented. Surface diffusion is positive at large dihedral angles. Unexpectedly, grain growth can be advantageous as well, provided that it acts continuously during the entire sintering cycle.